Literatur Review : Penerapan Pembelajaran Berdiferensiasi untuk Meningkatkan Hasil Belajar Siswa di Jenjang Pendidikan Menengah - Ivo Apristi (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2024)
This study aims to review scientific journals in order to collect relevant sources related to the differentiated approach. Differentiated learning is learning that accommodates, serves, and acknowledges the diversity of students in learning according to their readiness, interests, and learning preferences. The method used in writing this article is a literature review. The study began by looking for articles related to the research topic to be conducted. The criteria for scientific articles used as data are scientific articles sourced from national and international journals with updates in the last 10 years. This article reviews 12 articles related to differentiated learning in the context of mathematics education. This article aims to review the application of differentiated learning at the junior high and senior high school levels, with a focus on its impact on student learning outcomes. Based on a literature review of various related studies, this article discusses various differentiation strategies used by teachers, including the use of technology, material modification, and story-based approaches. Differentiated learning allows teachers to accommodate differences in students' abilities, interests, and learning styles, which contributes to improving academic understanding and student achievement. However, the implementation of this strategy is faced with challenges such as limited resources and resistance to policies. Based on this analysis, this article provides in-depth insights into the practice of differentiated learning has great potential to create a more inclusive learning environment and support the achievement of more optimal student learning outcomes in secondary education.